THERMAL DIFFUSIVITY MEASUREMENT OF SOLID USING PYROELECTRIC SENSOR - B. Z. Azmi; Y. T. Ling; M. Hashim; W. M. M. Yunus; M. M. Moksin (Universitas Gadjah Mada, 2002)
The recently developed pyroelectric spectroscopic technique has been used to measure the thermal diffusivity of solids. The method has been applied to conductors and insulator where by the thermal wave is measured at various lateral distances on the sample between laser illuminated line and pyroelectric sensor position. The thermal diffusivity is obtained from the gradient of the plot of thermal wave signal versus the lateral distance. A good agreement to the previously reported thermal diffusivity value has been obtained for aluminium, copper and spray paint that is 0.809 cm2s-1, 1.128 3cm2s-1 and 1.547 x 10-3 cm2s-1 respectively.